Resistivity Probability Tomography Imaging at the Castle of Zena, Italy. (23rd November 2009) - Compare, Vincenzo; Cozzolino, Marilena; Mauriello, Paolo; Patella, Domenico
Abstract : We present the results of an electrical resistivity investigation performed at Castle of Zena (Castello di Zena), a 13th-century fortress located between the towns of Fiorenzuola and Piacenza in the Emilia Romagna Region (Northern Italy), in the frame of a project of restoration. Dipole-dipole resistivity tomographies were planned in three areas suspected of containing buried archaeo-architectural remnants. Data analysis has been made using a 3D tomography imaging approach based on the concept of occurrence probability of anomaly sources in the electrical resistivity distribution. The 3D tomography has allowed three interesting anomaly source areas to be identified in the 1-2 m depth range below ground level. Subsequent excavations have brought to light a giacciara, that is, a brickwork room for food maintenance, a furnace, and the basement of a wing of the castle destroyed in the 18th century, exactly in correspondence with the anomaly sources detected by the resistivity tomography.